The case for a 3rd generation supraglottic airway device facilitating direct vision placement - Van Zundert, AAJ; Kumar, CM; Van Zundert, TCRV; Gatt, SP; Pandit, JJ (Springer, 2020)
Although 1st and 2nd generation supraglottic airway devices (SADs) have many desirable features, they are nevertheless inserted in a similar ‘blind’ way as their 1st generation predecessors. Clinicians mostly still rely entirely on subjective indirect assessments to estimate correct placement which supposedly ensures a tight seal. Malpositioning and potential airway compromise occurs in more than half of placements. Vision-guided insertion can improve placement. In this article we propose the development of a 3rd generation supraglottic airway device, equipped with cameras and fiberoptic illumination, to visualise insertion of the device, enable immediate manoeuvres to optimise SAD position, verify whether correct 1st and 2nd seals are achieved and check whether size selected is appropriate. We do not provide technical details of such a ‘3rd generation’ device, but rather present a theoretical analysis of its desirable properties, which are essential to overcome the remaining limitations of current 1st and 2nd generation devices. We also recommend that this further milestone improvement, i.e. ability to place the SAD accurately under direct vision, be eligible for the moniker ‘3rd generation’. Blind insertion of SADs should become the exception and we anticipate, as in other domains such as central venous cannulation and nerve block insertions, vision-guided placement becoming the gold standard.